2004
DOI: 10.1046/j.1365-2929.2004.01815.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the probability of first year medical student dropout in the UK: a logistic analysis for the intake cohorts of 1980-92

Abstract: Policies aimed at increasing the size of the medical student intake in the UK and of widening access to students from non-traditional backgrounds should be informed by evidence that student dropout probabilities are sensitive to measures of A-level attainment, such as subject studied and scores achieved. If traditional entry requirements or standards are relaxed, then this is likely to have detrimental effects on medical schools' retention rates unless accompanied by appropriate measures such as focussed stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
113
5
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(127 citation statements)
references
References 15 publications
6
113
5
3
Order By: Relevance
“…Only in a military medical program, female gender was found to be associated with higher risk for dropping out (Stetto et al 2004). In most medical universities, the drop-out ratio is usually lower for female students (Arulampalam et al 2004a(Arulampalam et al , 2004b(Arulampalam et al , 2007Andriole & Jeffe 2010). Hence, the situation in Austria (this study and Reibnegger et al (2011)) has been rather unique.…”
Section: Discussionmentioning
confidence: 99%
“…Only in a military medical program, female gender was found to be associated with higher risk for dropping out (Stetto et al 2004). In most medical universities, the drop-out ratio is usually lower for female students (Arulampalam et al 2004a(Arulampalam et al , 2004b(Arulampalam et al , 2007Andriole & Jeffe 2010). Hence, the situation in Austria (this study and Reibnegger et al (2011)) has been rather unique.…”
Section: Discussionmentioning
confidence: 99%
“…13,34,42 As is reported by Pryjmachuk et al, 13 age on entry is of moderate influence when it comes to timely completion of studies at the nursing department. On the other hand, Arulampalam et al,30 in their studies carried out in the UK, showed that students of medicine who are older than 21, bear a significantly higher risk of dropping out that younger students (OR=1.46), although these findings were not confirmed in their later studies. 31 The impact of age on attrition at medicine was also a subject of analyses of two studies performed in the United States 43,44 and one in Australia.…”
Section: Discussionmentioning
confidence: 86%
“…29 As is concluded by Ferguson et al 14 on the basis of systematic literature review, it is recommended to consider gender as one of the important variables in predictive studies at medical faculties. 14 As far as attrition is concerned, Arulampalam et al, 30 in their studies car ried out in the UK, found that men bear a greater risk of attrition than women (OR=1.19), although in their later works, the authors achieved contradictory results (OR=0.81). 31 Also, in case of a highly feminised profession such as nursing, it was observed that men bear a sig nificantly higher risk of dropping out than women.…”
Section: Discussionmentioning
confidence: 99%
“…Since dropping out represents an important educational problem, plenty of information on calculating the percentage of admitted students that drop out of medical school without completing their studies exists in the available literature [4,1922]. One interesting finding from this information is that the average percentages of dropping out varies among developed countries [3], which is only 11.1% normally, and for developing countries such as those in South America [17], dropout rates may range from 43 to 62%.…”
Section: Discussionmentioning
confidence: 99%